Implementation of the Student Support System in Schools of Sao Hai District under the Jurisdiction of Saraburi Primary Educational Service Area Office 1 - Chukua, Juree; Kohtbantau , Sunthon (Journal for Developing the Social and Community, 2022)
The research purposes were to study the implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1; and to compare the implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1, classified by the education level and work experience. The population was the teachers in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1. The sample group was the 108 teachers, determined by the Cohen table with confidence level 95 percent. The research instrument was the 5-level estimate rating scale questionnaire with Index of Item Objective Congruence between 0.80-1.00 and reliability 0.97. The data analysis statistics were the percentage, mean, standard deviation, and t-test (Independent Samples). The research findings were: The implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1 found the overall was at high level. The each aspect consideration found the three aspects were at high level according to descending mean were: the knowing students individually aspect, the screening students aspect, and the promoting student development aspect; and the two remaining aspects were at the moderate level according to descending mean were: the preventing and solving student problems aspect, and the transfer students aspect, respectively. The comparison results of the implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1 found: (1) the teachers with different of education level had the opinion on the implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1 found the overall and each aspect were different at statistics significance level .0, the teachers with a postgraduate degree were more opinionated than teachers with a bachelor’s degree; and (2) the teachers with different of work experience had the opinion on the implementation of the student support system in schools of Sao Hai District under the jurisdiction of Saraburi Primary Educational Service Area Office 1 found the overall and each aspect did not different.